«PURPLE MYSTERY» OR SIXTEEN-YEAR-OLD GIRL`S ACUTE INTERMITTENT PORPHYRIA - Беседина, Елена Алексеевна; Кравцова, Наталья Вячеславовна; Анчутин, Павел Евгеньевич; Беседина, Дарья Юрьевна; Нечаева, Валерия Дмитриевна; Юсуфова, Аделина Юсуфовна; Алиев, Баттал Нурадинович (Mother and Baby in Kuzbass, 2019)
The Patient G., 16 years old with polymorphic nonspecific complaints, since 2011.Objective – to analyse rare clinical case of the manifestation of acute intermittent porphyria (AIP) of sixteen-year-old girl, to trace the sequence of increase of clinical symptoms.Methods. To verify the diagnosis the method of determination of porphobilinogen (PBG) and δ-aminolevulinic acid (ALA) in urine was used. It is based on their separation by adsorption on columns with ion-exchange resin (ion-exchange column chromatography) with subsequent use of the Ehrlich reagent and measurement of results on a spectrophotometer in the wavelength range of 500-600 nm.Results. Acute intermittent porphyria was diagnosed confirmed by laboratory.Conclusions. At first patients get to the non-core departments, depending on the prevalence of main symptoms, many laboratories, even in large interregional clinics, do not have an opportunity the technique and special reagents of Ehrlich to determine porphyrins in the urine, the only pathogenetic method of treatment are hemе`s drugs, recently licensed in Russia.
Keywords: acute intermittent porphyria; heme; porphyrins; abdominalgia; red color of urine